Alignment of Management Priorities, Manufacturing Flexibility and Performance in Small Companies - Serrão, Rogerio Odivan Brito; Dalcol, Paulo Roberto Tavares (Brazilian Journal of Operations & Production Management, 2010)
Manufacturing flexibility can be used to achieve competitive advantage. Since flexibility is a relative concept, the level of required flexibility is defined by the market, i.e., it is defined by competitors and competitive environment. An important characteristic of manufacturing flexibility is its multidimensionality (dimensions and elements). Manufacturing flexibility has to be analyzed from the point of view of the dynamics of the relationships among its dimensions and the effective response a company has to give to all demands from its competitive marketplace. Depending on the management priorities, some manufacturing flexibility dimensions can be more emphasized and used as a competitive weapon to improve performance. This paper discusses the alignment (meaning the coherence between what is perceived and what is used) of actual manufacturing flexibility, considering the scope and achievability factors of five flexibility dimensions, and important aspects of management priorities and manufacturing performance based on a literature review and on a field work involving five small companies. Some related patterns are identified and show the managers’ perspective about these questions in the manufacturing flexibility context.